Perancangan Media Pembelajaran Matematika Berbasis WEB Menggunakan HTML dan CSS Kelas X di MAS M. Nadis bukittinggi - Mutiara Irce Marsela; Gusnita Darmawati; Sarwo Derta; Firdaus Annas (Jurnal Media Infotama, 2024)
The need for learning media to increase the motivation of students is essential to make them more interested in understanding the material presented. Based on the interview results with a Mathematics teacher at MAs M.Nadis Bukittinggi, it was found that current mathematics learning still uses basic media to support learning. However, during the learning process, students tend to feel bored when receiving the material taught, resulting in less than optimal delivery of the material by the teacher. Therefore, the author was interested in designing learning media that could help students understand the material more easily. The purpose of this research is to produce a web-based Mathematics learning media using HTML and CSS for the tenth grade at MAs M.Nadis Bukittinggi. The researcher utilized the Research and Development (R&D) approach. They applied the Hannafin and Peck development model, which consists of three stages: needs analysis, design, and development as well as implementation of learning. In this study, the product was tested through validity, practicality, and effectiveness. Based on the research results, it can be concluded that this web-based Mathematics learning media has been successfully designed and can be used to support mathematics learning. The product testing results conducted by the author showed that the validity test involving 3 experts produced a score of 0.82, which can be classified as a very valid category. The practicality test involving 2 practitioners produced a score of 0.84, which falls into the very high category. Meanwhile, the effectiveness test conducted with the participation of 11 evaluators produced a score of 0.89, which can be classified into the very effective category.